Analysis of CO2 Absorption in Gas/Liquid Membrane Contactors with Inserted Descending Hydraulic Diameters of 3D-Printed Turbulence Promoters - Chii-Dong Ho; Yi-Wun Wang; Zheng-Zhong Chen; Thiam Leng Chew (Membranes)
The decline in absorption flux across membrane modules is attributed to the increase in concentration polarization resistance in flat-plate membrane contactors for CO2 absorption using monoethanolamine (MEA) as the absorbent. Researchers have discovered that this effect can be mitigated by inserting turbulence promoters, which enhance turbulence intensity at the cost of increased power consumption, thereby improving CO2 absorption flux. The performance of flat-plate membrane contactors for CO2 absorption was further enhanced by reducing the hydraulic diameters of embedded 3D-printed turbulence promoters, considering the increased power consumption. The mass-balance modeling, incorporating chemical reactions, was developed theoretically and conducted experimentally on a flat-plate gas/liquid polytetrafluoroethylene/polypropylene (PTFE/PP) membrane module in the present study. A one-dimensional theoretical analysis, based on the resistance-in-series model and the plug-flow model, was conducted to predict absorption flux and concentration distributions. An economic analysis was also performed on modules with promoter-filled channels, considering different array configurations and geometric shapes of turbulence promoters, weighing both absorption flux improvement and power consumption increment. Device performances were evaluated and compared with those of modules using uniform promoter widths. Additionally, the Sherwood number for the CO2 membrane absorption module was generalized into a simplified expression to predict the mass transfer coefficient for modules with inserted 3D-printed turbulence promoters. Results showed that the ratio of absorption flux improvement to power consumption increment in descending hydraulic-diameter operations is higher than in uniform hydraulic-diameter operations.